An overview of the organizational model and structure of local radio in Catalonia - Lopes-da Silva, Elaine Aparecida; Martorell-Castellano, Cristina; Serra-Folch, Carolina (Estudios sobre el Mensaje Periodístico, 2026)
This research examines the organizational structure and human resources of local radio in Catalonia, including public, private, and community stations, in the context of technological transformation and digitalization of the sector. The main objective is to describe the internal organization of these stations, analyze the evolution of their staff over the last fifteen years, and determine the profile of the people in charge, paying special attention to the gender gap. To this end, a questionnaire was designed for managers of 227 Catalan radio stations, obtaining 155 valid responses (68.3 %). The questionnaire collected information on general data, hired and volunteer staff, programming, financing, organization, and future challenges. The results show that half of the stations have between one and four employees, while 27.1 % have no staff. Only 20.6 % have five or more employees. Volunteering plays a fundamental role: 86.5% of stations have at least five volunteers and 42.6 % have more than twenty, with this dependence being especially high in community stations. 68.4% of stations have not increased their staff in the last fifteen years, especially in public and community stations. Regarding management, 64.5̴ % of managers are men, and women, although better trained, occupy only 32.9 % of management positions, with greater inequality in private and community stations. The study concludes that Catalan local radio stations operate with very limited human resources and a heavy dependence on volunteers, which poses challenges of sustainability and professionalization, in addition to a persistent gender gap in management.
Keywords: local radio; volunteering; gender gap; organizational model; media